87 CTp11 CANCER/TESTIS-ASSOCIATED GENES FAMILY AS A POSSIBLE TUMOR VACCINE FOR LIVER NEOPLASIA. (1st January 2006) - Chiriva-Internati, M.; Grizzi, F.; Cobos, E.; Frezza, E.
Abstract : Purpose: SPANX/(CTp11) is a recently identified cancer-testis (CT) antigen in multiple myeloma, melanoma, and other tumors of unrelated histological origin. We here show that it is expressed at mRNA in neoplastic cells from up to 35% of patients affected by liver cancer. Since the expression of this tumor antigen has been demonstrated to be restricted in normal tissues, it seems to be an excellent target for tumor vaccine of liver cancer. Methods: PBMCs were separated from heparinized venous blood by density gradient centrifugation. DCs were differentiated from PBMC. Results: SPANX (CTp11) has been found to be expressed at mRNA level and at protein level by immunohistochemistry in neoplastic cells from up to 35% of patients affected by liver cancer. It contains functional cytotoxic T cell (CTL), supporting its use as a tumor vaccine. In this study, we determined the ability to generate CTp11-specific HLA-class I restricted CTLs from PBL of 5 patients, 3 consecutive SPANX (CTp11)+ patients and two SPANX (CTp11)-patients. Summary: Despite previous chemotherapy and the immunosuppression so often associated with liver cancer, CTL generation was successful in all 3 patients, suggesting the presence in the immune repertoire of SPANX (CTp11)-specific T cells in these patients, irrespective of the SPANX (CTp11) status of their tumors. Conclusion: These observations provide the basis for a clinical study aimed at inducing a cellular immune response directed at SPANX (CTp11)-positive liver cancer patients.